2006
DOI: 10.1007/s10875-006-9051-1
|View full text |Cite
|
Sign up to set email alerts
|

Similar CD19 Dysregulation in Two Autoantibody-Associated Autoimmune Diseases Suggests a Shared Mechanism of B-Cell Tolerance Loss

Abstract: : We report here that dysregulation of CD19, a coreceptor that augments B-cell receptor (BCR) signaling, occurs at two B-cell differentiative stages in patients with systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic autoantibody (ANCA) associated small vessel vasculitis (SVV). The naïve B cells of nearly all SLE and ANCA-SVV patients express approximately 20% less CD19 than healthy control (HC) B cells. In contrast, a subset of memory B cells of some SLE and ANCA-SVV Pts (25-35%) express two to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 55 publications
10
77
1
1
Order By: Relevance
“…Third, in transgenic mouse models, CD19 has been thought to be required for the development and maintenance of B-1a cells, 19 and CD19 dysregulation has been linked to autoantibody-associated autoimmune disorders, including systemic lupus erythematosus and antineutrophil cytoplasmic auotantibodies. 20 However, when B cells from CD19-deficient mice 17 were cultured, DS stimulated the expansion of CD5 ϩ B220 ϩ CD19 Ϫ B cells ( Figure 2E). This finding argues against a requirement for CD19 in the DS stimulation pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Third, in transgenic mouse models, CD19 has been thought to be required for the development and maintenance of B-1a cells, 19 and CD19 dysregulation has been linked to autoantibody-associated autoimmune disorders, including systemic lupus erythematosus and antineutrophil cytoplasmic auotantibodies. 20 However, when B cells from CD19-deficient mice 17 were cultured, DS stimulated the expansion of CD5 ϩ B220 ϩ CD19 Ϫ B cells ( Figure 2E). This finding argues against a requirement for CD19 in the DS stimulation pathway.…”
Section: Discussionmentioning
confidence: 96%
“…3). According to a recent study, the majority of CD19 + B cells are IgD + and CD27 -, indicating naive B cells [52]. They also reported CD19-high B cells as autoreactive memory B cells, and the frequency of this population correlates with disease activity [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, the majority of CD19 + B cells are IgD + and CD27 -, indicating naive B cells [52]. They also reported CD19-high B cells as autoreactive memory B cells, and the frequency of this population correlates with disease activity [52,53]. Also, active SLE disease has been shown to correlate with a high frequency of plasma cells, which express high levels of CD27 and low levels of CD19 [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we, and others, have shown a population of B cells which have 2-3 fold increased levels of CD19 compared to other B cells from the same patient or to healthy control B cells (CD19 hi cells) in SLE, ANCA-SVV, and CVID patients [30;32;33]. We previously reported that these CD19 hi B cells have an activated memory phenotype, are class switched, and show evidence of antigen selection [30]. We propose that the increased CD19 expression on CD19 hi memory B cells decreases their activation threshold leading to enhanced proliferation, survival, and plasma cell differentiation.…”
Section: Introductionmentioning
confidence: 84%
“…Five of the 10 patients from this study were patients continuing from the original study [30], and the other five were newly identified. Patients were included in this study after informed consent in accordance with our institutional internal review board, and fulfilled at least four of the established American College of Rheumatology 1997 revised criteria for SLE.…”
Section: Healthy Control and Patient Clinical Samples And Datamentioning
confidence: 99%